2015
DOI: 10.1161/atvbaha.115.305353
|View full text |Cite
|
Sign up to set email alerts
|

2015 ATVB Plenary Lecture

Abstract: Abstract-Rho-kinase (ROCKs) is an important downstream effector of the small GTP-binding protein Ras homolog gene family member A. There are 2 isoforms of ROCK, ROCK1 and ROCK2, and they have different functions in several vascular components. The Ras homolog gene family member A/ROCK pathway plays an important role in various fundamental cellular functions, including contraction, motility, proliferation, and apoptosis, whereas its excessive activity is involved in the pathogenesis of cardiovascular diseases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 201 publications
(296 reference statements)
0
33
0
Order By: Relevance
“…2,3,14,125,126 The beneficial effects of long-term inhibition of Rho-kinase for the treatment of cardiovascular disease have been demonstrated in various animal models, such as coronary artery spasm, arteriosclerosis, restenosis, ischemia/reperfusion injury, hypertension, PH, stroke, and cardiac hypertrophy/heart failure. 2,14,112,125 Gene transfer of dominant-negative Rho-kinase reduced neointimal formation of the coronary artery in pigs.…”
Section: Physiological and Pathological Roles Of Rhokinase In The Carmentioning
confidence: 99%
See 3 more Smart Citations
“…2,3,14,125,126 The beneficial effects of long-term inhibition of Rho-kinase for the treatment of cardiovascular disease have been demonstrated in various animal models, such as coronary artery spasm, arteriosclerosis, restenosis, ischemia/reperfusion injury, hypertension, PH, stroke, and cardiac hypertrophy/heart failure. 2,14,112,125 Gene transfer of dominant-negative Rho-kinase reduced neointimal formation of the coronary artery in pigs.…”
Section: Physiological and Pathological Roles Of Rhokinase In The Carmentioning
confidence: 99%
“…109,123 Indeed, Rho-kinase is an important therapeutic target in cardiovascular diseases. 2,3,14 On the basis of role of extracellular CyPA, we think that it is logical to consider that agents that prevent CyPA receptor binding and reduce circulating CyPA may have therapeutic potentials. Blocking the vicious cycle that increases ROS production through autocrine/paracrine CyPA signaling pathway mediated by Rho-kinase could be a novel therapeutic tool for controlling cardiovascular diseases (Figure 4).…”
Section: Rho-kinase-mediated Development Of Cardiovascular Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…41 Indeed, activation of eNOS catalyzes the production of NO, which is a crucial molecule for the maintenance of endothelial function and vascular homeostasis. 42 Indeed, Afolayan et al 43 demonstrated that phosphorylation of APMK and mitochondrial biogenesis are downregulated in fetal lambs with persistent PH of the newborn. In addition, eNOS phosphorylation in PAEC increased superoxide dismutase-2 levels and decreased the mitochondrial superoxide levels in this animal model of persistent PH of the newborn.…”
Section: Endothelial Ampk Downregulation Increases Pdgf-bb and Fgf-2 mentioning
confidence: 99%